A New Mn(II) Coordination Polymer Based on Dicarboxylate and Imidazole-Containing Ligand - Li, Yongfu (Asian Journal of Chemistry, 2014)
A new coordination polymer with the composition [Mn(ada)(bib)]n·2H2O (1) [H2ada = 1,3-Adamantane dicarboxylic acid and bib = 4,4'-bis(imidazolyl)-biphenyl], has been prepared by hydrothermal synthesis. Complex [Mn(ada)(bib)]n·2H2O (1), is Orthorhombic, space group Pnma with a = 14.352 (5) Å, b = 26.869 (5)Å, c = 11.576 (5) Å, V = 4464 (3)Å3, Z = 4, Mr = 904.89, Dc =1.346 g/cm3, F(000) = 1896 and μ = 0.357 mm-1. The final refinement gave R = 0.0583 and wR = 0.0712 for 2819 reflections with I > 2s(I). X-ray diffraction analysis reveals that complex 1 shows a two-dimensional (2D) layer structure.